Problematika Pelaksanaan Program Pengembangan Keprofesian Berkelanjutan Bagi Guru PAI di Kabupaten Banyuasin Sumatera Selatan - Tyara Maharani; Sartika Sartika; Muhammad Wardiansyah; Fitri Oviyanti; Maryamah Maryamah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This article aims to analyze the problems of implementing a sustainable professional development program for PAI teachers in Banyuasin Regency, South Sumatra. This research is a descriptive type of qualitative research with a field study approach. The data collection methods used in this research are interviews, observation and documentation, data analysis using data reduction, data presentation and verification. The results of this research are that sustainable professional development for PAI teachers will not be optimal if teachers cannot develop creativity within themselves. Creativity is an element of PAI teachers' independence. This program requires quite a long time and involves various quality improvement stakeholders so that it runs well. Lack of creativity creates its own problems for the teacher.